Children's Augmented Storying in, with and for Nature - Kristiina Kumpulainen; Jenny Byman; Jenny Renlund; Chin Chin Wong (MDPI AG, 2020)
Drawing on a relational ontology and scholarship of new literacies, we investigate the materiality and performativity of children's augmented storying in nature. Our study is situated in a Finnish primary school in which a novel, augmented reality application (MyAR Julle) was utilized as a digital storytelling tool for children (n = 62, aged 7-9), allowing them to explore, interact, and imagine in nature and to create/share their stories. The data corpus consists of their narrations of their augmented stories in nature, their augmented story artefacts, and video/observational data from their construction of such stories in nature. Narrative analysis reveals how the children's augmented storying in nature was performed through playful, affective, and sensuous, identity, cultural, and critical literacies, which were imaginatively constructed into being at the nexus of their sensed reality and fantasy. These literacies make visible human-material-spatial-temporal assemblages during which the children played with/through the augmented character Julle, felt and sensed with/through Julle, and re-storied their experiences, cultural knowledge, and identities with/through Julle. They also engaged in critical thinking with/through Julle. The study contributes to knowledge on the meaning of materiality in children's storying in, with, and for nature and the educational possibilities of augmented storying for children's (eco)literacies.